(untitled) (Journal of Plant Disease Sciences, 2019)
Coffee brown eye spot caused by Cercospora coffeicola Berk. &Cke. is one of the important disease in coffee nurseries and in early stage on field plants of both arabica and robusta coffee cultivars. On infected leaves the symptoms observed as circular necrotic spots with colouration from gray to brown, frequently surrounded by a yellow halo. Further, necrotic spots increase in size and such spot on leaves coalesce and turn yellow. Infected leaves reduce the photosynthetic area and such seedlings shows stunted growth and may not attain desirable height. Severe infections lead to premature defoliation. In the present study,efficacy of eight fungicides were tested against coffee brown eye spot disease for two consecutive seasons viz., 2017-18 & 2018-19 under nursery conditions at Central Coffee Research Institute, Chikkamagaluru District, Karnataka.The results of pooled analysis 2017-18 and 2018-19 indicated that least (4.23%) disease incidence was recorded in tebuconazole 25.9 EC (1.0 ml/L.) followed by trifloxistrobin 25% + tebuconazole 50% WG (2.0 g/L.) (4.26%). Highest incidence (22.78%) was recorded in untreated control.The experiment results revealed that tebuconazole 25.9 EC and trifloxistrobin 25% + tebuconazole 50% WG could be used for the control of brown eye spot disease of coffee.